Contrasting effects of sampling scale on insect herbivores distribution in response to canopy structure - Frederico S. Neves; Carlos F. Sperber; Ricardo I. Campos; Janaína P. Soares; Sérvio P. Ribeiro (Revista de Biología Tropical, 2013)
Species diversity of insect herbivores associated to canopy may vary local and geographically responding to distinct factors at different spatial scales. The aim of this study was to investigate how forest canopy structure affects insect herbivore species richness and abundance depending on feeding guilds´ specificities. We tested the hypothesis that habitat structure affects insect herbivore species richness and abundance differently to sap-sucking and chewing herbivore guilds. Two spatial scales were evaluated: inside tree crowns (fine spatial scale) and canopy regions (coarse spatial scale). In three sampling sites we measured 120 tree crowns, grouped in five points with four contiguous tree crowns. Insects were sampled by beating method from each crown and data were summed up for analyzing each canopy region. In crowns (fine spatial scale) we measured habitat structure: trunk circumference, tree height, canopy depth, number of ramifications and maximum ramification level. In each point, defined as a canopy region (coarse spatial scale), we measured habitat structure using a vertical cylindrical transect: tree species richness, leaf area, sum of strata heights and maximum canopy height. A principal component analysis based on the measured variables for each spatial scale was run to estimate habitat structure parameters. To test the effects of habitat structure upon herbivores, different general linear models were adjusted using the first two principal components as explanatory variables. Sap-sucking insect species richness and all herbivore abundances increased with size of crown at fine spatial scale. On the other hand, chewer species richness and abundance increased with resource quantity at coarse scale. Feeding specialization, resources availability, and agility are discussed as ecological causes of the found pattern. La diversidad de especies de insectos herbívoros asociados con el dosel puede variar geográficamente y responder a distintos factores a diferentes escalas espaciales. El objetivo de este estudio fue investigar cómo la estructura del dosel afecta la riqueza de especies de insectos herbívoros y la abundancia en función la especialización alimenticia. Se evaluó la hipótesis que propone que la estructura del hábitat afecta en forma diferente la riqueza y abundancia de especies de insectos que se alimentan de savia y la de especies herbívoras masticadoras. Dos escalas espaciales fueron evaluadas: el interior de las copas de árboles (escala fina) y regiones del dosel (escala gruesa). En tres sitios de muestreo medimos 120 copas de árboles, agrupadas en cinco puntos con cuatro copas de árboles contiguas. Los insectos fueron muestreados golpeando las copas y los datos fueron sumados para analizar cada región del dosel. En las copas (escala espacial fina) medimos la estructura del hábitat: circunferencia del tronco, altura del árbol, profundidad del dosel, número de ramificaciones y máximo nivel de ramificación. En cada punto, definiendo una región del dosel (escala gruesa), medimos la estructura del hábitat usando un transecto cilíndrico vertical: riqueza de especies árboles, área foliar, sumatoria de altura de los estratos y máxima altura del dosel. Fue realizado un anlisis de componentes principales basado en las variables medidas para cada escala espacial para estimar los parámetros de la estructura del hábitat. Para probar los efectos de la estructura del hábitat sobre los herbívoros, se ajustaron diferentes modelos lineares generales usando estos componentes principales como variables causales. La riqueza de especies chupadoras de savia y la abundancia de todas las especies herbívoras se incrementaron con el tamaño de la copa en la escala espacial final. Por otro lado, la riqueza y abundancia de especies masticadoras incrementaron con la complejidad de la estructura del hábitat en la escala más gruesa. La especialización alimenticia, la disponibilidad de recursos y la movilidad son propuestas como los factores ecológicos que explican los patrones observados.